Monumen Perjuangan Masyarakat Cupak Ditinjau Dari Segi Bentuk, Fungsi Dan Tata Letak - Dinda Fitria; Maulid Hariri Gani; Rica Rian (V-art: Journal of Fine Art, 2021)
This study discusses the Cupak Community Struggle Monument in Solok Regency in terms of form, function, and layout. In addition, we briefly discuss the brief history behind the monument's establishment. This study uses a qualitative approach which includes observations, interviews, literature studies, and research is carried out directly to the field, namely to the Cupak area in Solok Regency, West Sumatra. Based on the results of the research conducted, it is known that the construction of the Cupak Community Struggle Monument aims to commemorate the period of the Cupak people's struggle against the Japanese army, and the shape of the monument is a visual representation of 3 warriors including statues consisting of figures dressed in Indonesian soldiers, Japanese soldiers, and community warrior. The layout of the Cupak Community Struggle Monument is closely related to the function of the monument itself, a monument that has a social function and a physical function, namely a monument which, if created and viewed on a public scale, means that it can reach the wider community.